Relevansi Nilai Laba Akuntansi pada Aksi Stock split : Pendekatan Model Harga Dan Return - - Linda; Endang Surasetyo Ningsih (Conference In Business, Accounting, And Management (CBAM), 2012)
This study is aimed to prove value-relevance of earning per share that used by investors in decision making around stock split announcements. Both price and return models as a valuation models are commonly used in value-relevance studies. The Price model shows that value-relevance of earning per share has a positive correlation and statistically significant association with stock price, it would explain that earning information relates with stocks price due to the anticipate components of future expectation net cash flow. While, return model shows that value-relevance of earning per share has no correlation with stock return, because of the accounting recognition lag. The actual return-earning relation is considered to be more forward looking, furthermore this model is free from scale effect problem.Keywords: value-relevance, earning, price, return